2010
DOI: 10.1364/oe.18.006703
|View full text |Cite
|
Sign up to set email alerts
|

Photoanisotropic polarization gratings beyond the small recording angle regime

Abstract: Abstract:Polarization gratings can be realized by polarization holographic recording in photoanisotropic materials. In this paper, we study two types of polarization gratings. One is recorded with two orthogonally circularly (OC) polarized beams and the other one with two orthogonally linearly (OL) polarized beams. The interference of both cases is explored beyond the small recording angle regime. A novel method is proposed to represent the polarization states of the modulation. The diffraction by polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
11
1
1
Order By: Relevance
“…With the analysis of surface-relief gratings from Section 3 in mind, we may wonder whether these properties are not just a consequence of the fact that the polarization gratings that were studied could be considered as thin. In this section we experimentally verify the good angular acceptance that was found numerically by Xu et al [11] for large-period polarization gratings and study to what extend it still holds for small periods, useful for in-coupling applications (Λ λ ).…”
Section: Polarization Gratingssupporting
confidence: 66%
See 3 more Smart Citations
“…With the analysis of surface-relief gratings from Section 3 in mind, we may wonder whether these properties are not just a consequence of the fact that the polarization gratings that were studied could be considered as thin. In this section we experimentally verify the good angular acceptance that was found numerically by Xu et al [11] for large-period polarization gratings and study to what extend it still holds for small periods, useful for in-coupling applications (Λ λ ).…”
Section: Polarization Gratingssupporting
confidence: 66%
“…η 0 thus vanishes when the thickness and wavelength are related by d = λ /2∆n. Furthermore, previous simulations indicated that the diffraction efficiency of polarization gratings is relatively insensitive to the angle of incidence [11]. Based on these arguments, they seem to be a good choice as gratings for in-coupling applications.…”
Section: Polarization Gratingsmentioning
confidence: 84%
See 2 more Smart Citations
“…An in-house numerical code based on FEM is used to simulate the light interaction with the multilayer stack [5][6][7]. In brief, FEM solves a boundary value problem for the vector Helmholtz equation for either the electric or magnetic field in a confined computational domain.…”
Section: Fem For Rigorous Electromagnetism Modelingmentioning
confidence: 99%